EChO: Exoplanet characterisation observatory - Tinetti, G; Beaulieu, J; Henning, T; Meyer, M; Micela, G; Ribas, I; Stam, D; Swain, M; Krause, O; Ollivier, M; Pace, E; Swinyard, B; et al. (2012)
A dedicated mission to investigate exoplanetary atmospheres represents a major milestone in our quest to understand our place in the universe by placing our Solar System in context and by addressing the suitability of planets for the presence of life. EChO-the Exoplanet Characterisation Observatory-is a mission concept specifically geared for this purpose. EChO will provide simultaneous, multi-wavelength spectroscopic observations on a stable platform that will allow very long exposures. The use of passive cooling, few moving parts and well established technology gives a low-risk and potentially long-lived mission. EChO will build on observations by Hubble, Spitzer and ground-based telescopes, which discovered the first molecules and atoms in exoplanetary atmospheres. However, EChO's configuration and specifications are designed to study a number of systems in a consistent manner that will eliminate the ambiguities affecting prior observations. EChO will simultaneously observe a broad enough spectral region-from the visible to the mid-infrared-to constrain from one single spectrum the temperature structure of the atmosphere, the abundances of the major carbon and oxygen bearing species, the expected photochemically-produced species and magnetospheric signatures. The spectral range and resolution are tailored to separate bands belonging to up to 30 molecules and retrieve the composition and temperature structure of planetary atmospheres. The target list for EChO includes planets ranging from Jupiter-sized with equilibrium temperatures Teq up to 2,000 K, to those of a few Earth masses, with Teq ∼ 300 K. The list will include planets with no Solar System analog, such as the recently discovered planets GJ1214b, whose density lies between that of terrestrial and gaseous planets, or the rocky-iron planet 55 Cnc e, with day-side temperature close to 3,000 K. As the number of detected exoplanets is growing rapidly each year, and the mass and radius of those detected steadily decreases, the target list will be constantly adjusted to include the most interesting systems. We have baselined a dispersive spectrograph design covering continuously the 0. 4-16 μm spectral range in 6 channels (1 in the visible, 5 in the InfraRed), which allows the spectral resolution to be adapted from several tens to several hundreds, depending on the target brightness. The instrument will be mounted behind a 1. 5 m class telescope, passively cooled to 50 K, with the instrument structure and optics passively cooled to ∼45 K. EChO will be placed in a grand halo orbit around L2. This orbit, in combination with an optimised thermal shield design, provides a highly stable thermal environment and a high degree of visibility of the sky to observe repeatedly several tens of targets over the year. Both the baseline and alternative designs have been evaluated and no critical items with Technology Readiness Level (TRL) less than 4-5 have been identified. We have also undertaken a first-order cost and development plan analysis and find that EChO is easily compatible with the ESA M-class mission framework. © 2012 Springer Science+Business Media B.V.